Inovação e universidade: uma análise da cultura organizacional da Universidade Estadual de Ponta Grossa - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
The work will show the organizational culture of the State University of Ponta Grossa. With that in mind, it will make an analysis of the negotiations produced between the university and companies of the region for the purpose of licensing technology, as well as its internal regulations and news from their website, in a way to understand their values, precepts and subjective assumptions. There are conflicts in the relationship between universities and companies that lead to difficulties in the firmament of technology licensing contracts. Such a stumbling block may have established reasons in the university's culture of innovation, not prepared for participation in socio-economic development, by a tradition of elite formation. The method of used for the confection of the reserarch it’s a case study, using bibliography, as well as raising primary data by means of data collection of the databases of the State University of Ponta Grossa. At the end of the research, it was concluded that the institution has spent the last few years improving its values and subjective assumptions. However, some problems have been found in reference to the institution's precepts.
Keywords: Propriedade intelectual; Transferência de Tecnologia; Cultura organizacional; Autonomia universitária; Intelectual property; Technology transfer; Organizacional culture; University autonomy; CNPQ::CIENCIAS SOCIAIS APLICADAS